Paraspinal radiation recall myositis after gemcitabine for pancreatic adenocarcinoma. Issue 5 (4th May 2021) - Barrios-Anderson, Adriel; Radhakrishnan, Reshmitha; Yu, Esther; Shimanovsky, Alexei
Abstract : Radiation recall (RR) is a chemotherapy-induced reaction that leads to inflammation and necrosis in previously irradiated tissue. Gemcitabine is a cytidine analogue that is often used in conjunction with nab-paclitaxel in the treatment of pancreatic cancer. Herein, we present a case of a 56-year-old woman with stage III pancreatic adenocarcinoma diagnosed with gemcitabine-induced RR when she presented with lower back pain and new rim-enhancing collections within the right and left paraspinal musculature 5 months after radiation therapy to the pancreas. A PubMed search was performed for 'Radiation Recall Myositis' and a complete literature review performed. This case and review of the literature of published cases of RR myositis highlight the clinical course and presentation of RR myositis. This review highlights the importance of considering RR in the differential diagnosis when patients who are undergoing chemotherapy and radiation present with inflammatory changes in previously irradiated areas.